SISTEM INFORMASI SIMPAN PINJAM KOPERASI BERBASIS WEB (Studi Kasus : Koperasi Sejahtera PT. Induro Internasional Tangerang) - Eva Rahmawati; Tri Retnasari; Dwie Arifianto (JURNAL TEKNIK KOMPUTER AMIK BSI, 2016)
Information and communications technology is now being liberated part of the archiving process. In a saving and sales, information technology is needed to keep the document from damaged or lost. The purpose of this cooperative information system development is to accelerate the employeein the process of data processing and the saving and loan, and facilitate members to get information about transactions within the cooperative.Cooperative Sejahtera PT. International Induro need a solution to overcome the shortcomings. The right solution is to implement a computerized system of savings and loans that have been programmed so as to simplify the process of data processing savings and loan cooperative members. With the right data processing system will generate accuracy in preparing reports that are used as information for the cooperative Sejahera PT. International Induro. With the establishment of savings and loan information system to facilitate the processing of transaction data members, so as to produce a report that is fast, precise, and accurate in accordance with what is needed. With so Cooperative Sejahera PT. International Induro will be easier to improve system performance in order to more optimally. Keywords: Design of Information Systems, Cooperatives, Savings and Loan